FACTORS AFFECTING THE DECISION ON CHOOSING LOGISTICS SERVICE PROVIDER IN FOOD AND BEVERAGE MANUFACTURING INDUSTRY - โฆสิตธัญญสิทธิ์ กาญจน์สิตา; กุณฑลบุตร ชนงกรณ์ (RMUTT Global Business and Economics Review, 2016)
The purpose of this research were to study the characteristics of the organizations of user in the food and beverage manufacturing industry as well as to study the marketing mix factor (7Ps) of the logistics users affecting the decisions to choose the nationality of the logistics service activities. The questionnaire was used as an instrument for data collection from the 370 samples. Descriptive and inferential statistics used for data analysis included frequency, percentage, mean, standard deviation, One-way ANOVA, independent samples ttest, chi-Square, and binary logistic regression at significance level of 0.05 The results revealed that the majority of participants used to use logistics services, and they still use the services whereas the numbers of the users tend to increase. Most of them decide to mainly use the services from the transportation service providers. Furthermore, the users choose the service providers who are the multinational corporations have more potential than Thai corporations in terms of the service quality, modern technology, and investment and networking with the organizations of the users. The results of the hypothesis testing indicated that the different characteristics of the organization in term of the registered capital, the scope of service requirement, the duration of the business establishment and the size of the business have significant impact on the selection of service providers. According to the correlation analysis the characteristics of the organizations the registered capital, the scope of service providers found that the varies in the registered capital, the scope of service, nationality the size of business and marketing Factor han relationship with selecting service provder.